Testosterone levels correspond with increased ventral striatum activation in response to monetary rewards in adolescents - Op de Macks, Zdeňa A. (Dev Cogn Neurosci, 2011)
Risk taking is an integral part of learning and development, particularly during adolescence the prevalence of risky behaviors peak. It is hypothesized that the tendency to take risks is related to pubertal maturation, where there is interplay between gonadal hormones, the neural mechanisms that underlie affective (e.g., reward) processing, and risky behavior. To test this hypothesis, fifty healthy adolescents (aged 10–16 years; 33 girls, 17 boys) at different stages of puberty performed a gambling task while lying in the MRI scanner, and provided saliva samples for hormone assessment. Gonadal hormone levels were correlated with the neural response to receiving a monetary reward. Results showed that testosterone level correlated positively with activation in the striatum for both boys and girls, suggesting that individual differences in hormones at puberty are related to the way adolescents respond to reward, which can ultimately affect risk-taking behavior.